Klienci w controllingu sprzedaży - Iwaniec, Magdalena Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper deals with both sales controlling as the concept which supports sales management and customers as the most important element of environment. A point of contact is customer orientation, which is one of controlling assumptions and also sales controlling. Among sales controlling tools we can distinguish the group in which a customer is the main point. The tools are for example Customer Relationship Management and portfolio analyses. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 96-102